Apigenin Inhibits the Histamine-Induced Proliferation of Ovarian Cancer Cells by Downregulating ERα/ERβ Expression - Liu, Manman; Zhang, Yani; Xu, Qiqi; Liu, Guirong; Sun, Na; Che, Huilian; He, Tao (Frontiers in Oncology, 2021)
Background Apigenin, as a natural flavonoid, can affect the development of a variety of tumors, but its role in ovarian cancer is still unclear. In addition, studies have shown that mast cells, as a component of the tumor microenvironment, can affect the progression of ovarian cancer, but the mechanism needs further exploration. Method and results In this study, transcriptomics analysis was performed on the collected human tissue samples of ovarian cancer, and we found that the expression of genes related to mast cells in ovarian cancer tissues are diverse. Then we selected histamine released by degranulation of mast cells as the research object, and explored whether it affects the development of ovarian cancer through human sample analysis and cell experiments. It was found that compared with normal ovarian tissue, the expression of histamine in cancer tissue was significantly higher, and a certain concentration of histamine do promote the proliferation of ovarian cancer cells. In addition, we found that in cancer tissues, the relative expression of Estrogen receptor α (ERα) and Estrogen receptor β (ERβ) changes significantly, and inhibition of ERα or activation of ERβ can inhibit the proliferation of ovarian cancer cells induced by histamine. Last, we study apigenin’s effect on ovarian cancer and its mechanism. Conclusion Our research revealed that apigenin slows down the promotion of histamine on the development of ovarian cancer by down-regulating ERα/ERβ, providing a potentially effective treatment strategy for ovarian cancer.